The Window Distribution of Idealized TCP Congestion Avoidance with Variable Packet Loss - MISRA, Archan (Institutional Knowledge at Singapore Management University, 1999)
This paper analyzes the stationary behavior of the TCP congestion window performing ideal congestion avoidance when the packet loss probability is not constant, but varies as a function of the window size. By neglecting the detailed window behavior during fast recovery, we are able to derive a Markov process that is then approximated by a continuous-time, continuous state space process. The stationary distribution of this process is analyzed and derived numerically and then extrapolated to obtain the stationary distribution of the TCP window. This numerical analysis enables us to predict the behavior of the TCP congestion window when interacting with a router port performing early random drop (or random early detection) where the loss probability varies with the queue occupancy